Pepparmyntans bioaktiva ämnen - hur påverkar de människors hälsa? - Pallin, Anton (SLU/Dept. of Food Science, 2010)
Since early civilization, herbal tea has been used as remedies for an abundance of different diseases. Among these herbal remedies, peppermint (Mentha piperita) was used for its effect on bowel related ailments. Even though peppermint was not described until late 17th century, it has been used since 1000 years before Christ by the Egyptians. In present day it is still considered a remedy for stomach pain etcetera, and much of the recent research is concentrated on the positive effects of peppermint on pain and bowel diseases. A large section of the research is also reviewing positive effects of peppermint on cancer, allergy and also on its potential as antibacterial agent. The substances that are known to have a possible effect on these diseases are polyphenols, which acts as antioxidants. Examples of such polyphenols are luteoline and other flavanoids. Luteoline seems to protect against the formation of tumors by inhibiting cell proliferation and inducing apoptosis. It also seems to lower the amount of histamine that is released from mast cells, which reduce the amount of allergic inconveniences. The main volatile components in peppermint, menthol and menthone, also seem to participate to some of the positive properties of peppermint. Menthol and menthone acts as analgesics by influencing the calcium channels in muscle tissue. Even though a lot of experiments have been performed, the number of human studies and clinical studies are limited. Such studies are required to enable a definitive conclusion to be drawn about peppermints health effects. Peppermint seems to have a lot of positive effects, but caution should always be made before conducting any remedies. Herbal remedies can have negative effects if the remedy is prolonged or is carried out in combination with medicines